Strategi Pemasaran Produk Arrum BPKB Pada Pegadaian Syariah CPS Margonda - Masitoh Syahidah; Azis Budi Setiawan; Endang Ahmad Yani (Jurnal Ekonomi dan Perbankan Syariah, 2018)
This research is a quantitative research, which aims to know the marketing strategy that can be done by shariah pawnshops of ARRUM BPKB financing products. The population in this study is all employees associated with ARRUM products. While the sample used in this study is saturated samples. The type of data that the author uses is the primary and secondary data types. The method used to formulate strategies using SWOT Analysis. The results of this study indicate that the product ARRUM BPKB located in Quadrant I is in Progressive conditions. Under these conditions, the S-O strategy is the right one to apply. And based on the calculation of QSPM, the priority of strategy with the highest Value of Attractiveness (TAS) is the socialization of cheaper ujroh cost to UMKM in a more massive way.